Pain Severity Ratings Among Patients with Comorbid Chronic Pain and PTSD: A Retrospective Cohort Study - Lily Charron; Eduardo Espiridion (International Journal of Medical Students)
Background: Posttraumatic stress disorder (PTSD) is a psychiatric disorder that may occur after experiencing or witnessing a traumatic event. PTSD is characterized by physiological symptoms such as sleep disturbances and hyperarousal. One understudied symptom in PTSD patients is chronic pain (CP). Acute pain can lead to CP when it persists beyond adaptation. The interconnection between stress and pain has been well-established in fields of neuroscience and psychology, though we still do not fully understand the nature of this clinical relationship.